ANALISIS KOMPENSASI TERHADAP PENINGKATAN PRODUKTIVITAS KERJA KARYAWAN PADA HOTEL AMBUN SURI BUKITTINGGI - Riyani, Raftul Fedri, (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
The compensation is all the income in the form of money, goods directly or indirectly received byemployees as a reward for services rendered to the company. Ambun Suri Hotel as a budget hotel witha high level of competition between the Hotel-Hotel and other companies need to improve theiremployee productivity through motivational processes are realized with compensation eventuallyexpected to increase the productivity of its employees. To provide the motivation to work productivityof employees can proceed smoothly Ambun Suri Hotel provide direct compensation (base salary, mealallowance, bonus and transport) and indirect (social security benefits). This study aimed to analyzedthe compensation to the increased productivity of employees in Ambun Suri Hotel Bukittinggi.This study used descriptive qualitative method, with the number of sample as many as 19 people, were used inthis study is by observation, questionnaire and documentation. This study was conducted in August 2016 and islocated in Ambun Suri Hotel Bukittinggi. Data obtained using a number of instruments that constitute thequestionnaire and processed using variable frequency analysis for the purposes of this study.Keyword: compensation and employee productivity